2019
DOI: 10.1080/17461391.2019.1600587
|View full text |Cite
|
Sign up to set email alerts
|

Do generations differ in sports participation and physical activity over the life course? Evidence from multiple datasets

Abstract: Generational differences in health-related factors will affect forecasts of future disease patterns and health care needs. We studied whether participation in sports activity and being physically active are different between 10-year generations over a part of their life course. We used three different datasets on Dutch adults: a cohort study running for 20 years, the Doetinchem Cohort Study (DCS), multiple yearly databases (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another hypothesis regarding the association of early sports participation with younger aged adults could be related to an increase in sports participation in youth in recent decades, as observed by Mathisen et al, 46 which reported an increase of up to 20% in sports participation from 1985/1986 to 2014. Convergently, van Oostrom et al 47 observed an increase in self-reported sports participation for many decades, which may be related to higher sports participation in younger adults than older ones.…”
Section: Discussionmentioning
confidence: 98%
“…Another hypothesis regarding the association of early sports participation with younger aged adults could be related to an increase in sports participation in youth in recent decades, as observed by Mathisen et al, 46 which reported an increase of up to 20% in sports participation from 1985/1986 to 2014. Convergently, van Oostrom et al 47 observed an increase in self-reported sports participation for many decades, which may be related to higher sports participation in younger adults than older ones.…”
Section: Discussionmentioning
confidence: 98%
“…This could be simply an effect of ageing, but also there could be differences between cohorts. Older generations were found to engage in less physical activity than recent generations [ 52 ] and previous research reported the tendency to maintain active behaviors over the life course [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect to highlight is that participants who reported early sports practice were significantly younger than those who reported not having early sports practice (36.4 vs. 50.3 years of age). In addition, it has been reported that self-reported sports participation has been increasing for many decades [ 52 ], and, in this sense, it is possible that younger adults were more likely to have practiced sports during their youth than older adults.…”
Section: Discussionmentioning
confidence: 99%